Between historical memory and struggle for ellenbogenraum: Max Weber on nation - Norkus, Zenonas (Politologija, 1999)
The article can be read as an answer to the remark of Perry Anderson: "whereas Weber was so bewitched by the spell of nationalism that he was never able to theorize it, Gellner has theorized nationalism without detecting the spell". (Anderson P. A Zone of Engagement. London: Verso, 1992. P. 205). A reason for such opinion can be Weber's scepticism about the very possibility to define in a scientifically useful way the concepts of "ethnicity" and "nation", expressed in his Economy and Society. He provides nevertheless both the definitions of those phenomena and the suggestions for the viable explanatory and predictive theory about them. The task of the article is limited to the discussion of Weber's suggestions on nations and nationalism. The main thesis is that those suggestions point in diverging directions: whereas Weber's statements in Economy and Society constitute an outline of the political-sociological theory of nations and nationalism, his early work (1892-1899) contains a rather different approach which is qualified as political-economical.In the first approach, elaborated by Randall Collins (in his Weberian Sociological Theory. Cambridge: Cambridge UP, 1986. P. 145ff.), nations are conceived as groups competing for the positional good "prestige of power" or "prestige of culture" in the international competition, each of them striving after the highest possible place in the "League of Nations". The attachments of the individuals to their national communities is explained by dynamics of success or failure of those communities in the competition.In the early work of Weber, the nations are conceived however rather Darwinistically as the communities organized in an optimal way for the collective rent-seeking activities—the struggle for the enlargement and monopolization of the "vital space" (Ellenbogenraum; Ernährungsspielraum)—in the globalized Malthusian world drifting to the global stationary state. Besides the investigation of the roots of Weber's early concept of nation in the tradition of classical political economy, the article contains the reconstruction of Weberian concept of nationalism as ideological principle, based both on Weber's statements and on Collins' elaboration of Weber's political-sociological concept of nation.This principle prescribes the limitation of the solidarity duties to the members of the own "national community", interpreting those duties as analogous to those of team solidarity in command sport.The article consists of three sections. The first one exposes Weber's political-sociological, the second one—the political-economical concept of nation, and the third one contains the assessment of Weber's ideas with respect to the dichotomies in the current ethnicity and nationalism studies (perennialism-modernism; primordialism-instrumentalism; culturalism-naturalism) and to its stimulation potential for the contemporary research. Weber's work on ethnicity and nationalism is qualified as culturalist (the early work containing elements of naturalism) and instrumentalist.Weber's early concept of nation is modernist, presupposing the world with the world market and the globalized struggle for "vital space". The politico-sociological concept of nation sits uneasy with the very dichotomy of perennialism and modernism because Weber considers nation as coeval not with the industrialization but with the existence of the system of competing states.The reading of Weber helps to identify the defect in the prevailing modernity concept of nationalism (represented exemplarily by the work of Ernest Gellner, Eric Hobsbawm, and Benedict Anderson) consisting in its "ruritanocentrism": ignoring the imperialist and hegemonic nationalism of the old great nations. Although Weber's prognosis of the global tendencies was false (the modern world is not a Malthusian one), Weber's early intuitive idea of nation as broadest rent-seeking group in the global competition is potentially fruitful and still waits for transformation into analytical model.
Keywords: -